Geometrical modifications of the anchor impeller to enhance the overall performances in stirred tanks - Ameur, Houari; Kamla, Youcef (Instal, 2020)
The performance of modified anchor impellers in stirred tanks is investigated. The classical anchor impeller is taken as a reference, then the upper part of the blade arm is curved at different degrees (α). Three geometrical configurations are explored, namely: α = 0° (which corresponds to the standard shape of anchor impellers), 45°, and 90°. The study is achieved numerically by using a finite volume method based CFD tool. The case of highly viscous Newtonian fluids under laminar flow conditions is considered. From the obtained results, the newly modified anchor impeller has allowed an enhancement in the axial circulation of liquid and a reduction in power requirements. The curved blade with 90° yielded a decrease in power number by about 2.5%, compared to the classical anchor impeller.